Mental Foramen as a Guide to Establish Sexual Dimorphism among Eastern Indian Population: An Observational Cross-sectional Study on Dry Bones - Soumali Biswas; Joydip Saha; Arijit Majumdar; Ratnadeep Poddar; Suchismita Ghosh; Maitreyee Kar (Journal of the Scientific Society)
Context: The study deals with a role of mental foramen in determining the sexual dimorphism of mandibles as well as generating the sufficient data for the dental surgeons regarding location and measurements of the same. Aims: The aim of the study was to determine the location of mental foramen with respect to the different bony points of mandible and the presence of accessory foramen, if any and to establish sexual dimorphism among mandibles in relation to mental foramen and assessing the role of mento-submental angle for the same. Settings and Design: An observational cross-sectional study was conducted at Medical Colleges of West Bengal. Materials and Methods: Two hundred and eighty dry mandibles were used. Digital images were captured with digital camera after placing the bones in anatomical position for suitable views. Measurements were taken with the help of ImageJ software. Statistical analysis was performed using the SPSS software. Statistical Analysis Used: Measures of central tendency were determined. Significance was tested using the Chi-square test or unpaired Student’s t test, as applicable. Results: Most of the mental foramina were in line with the second premolar tooth or between the first and second premolars. Distance from the alveolar margin and the diameters of foramen were statistically significant among the genders. Mento-submental angle was significantly lower in males as compared to females being <115° and >115°, respectively. The prevalence of accessory mental foramen was very low in both genders. Conclusions: Sexual dimorphism can be well established from the morphometry of mental foramen of mandibles in the Eastern Indian population.